Perspectives on the Irish Language in Education in the Early- to Mid-Twentieth Century - Ó Murchadha, Noel (My University, 2024)
Many Minority language revitalization movements globally strive for the status the Irish language today enjoys in formal education: as a core subject in mainstream primary and post-primary schools, as a medium of instruction in a mature system of immersion education, as a required matriculation subject for the constituent universities of the National University of Ireland and for entry into initial teacher education for primary school teaching. Furthermore, a dedicated policy for Gaeltacht education has been in operation since 2017, a new policy framework for Irish-medium education outside the Gaeltacht has recently been published, and a new national plan is in development for Irish language provision in early learning and care and for school-age childcare. In addition, the Primary Language Curriculum and the Junior Cycle post-primary specifications for Irish differentiate between the needs of students who learn through Irish and those who learn through English. Likewise, a new specification for Irish at Senior Cycle post-primary is in development and will likely make similar alternative provisions for students in Irish-medium versus students in English-medium settings.
PUBLISHED
Keywords: Identities in Transformation; Making Ireland